Falling In Love Outward: Pantheism and Spiritual Well-Being - Wager, Khai (AGATHEOS – European Journal for Philosophy of Religion, 2024)
This paper presents a pantheistic account of spiritual well-being drawn from the life and works of poet Robinson Jeffers. The account is based on a general conceptualisation of the spiritual life according to which it has three components: a conception of ultimate reality, a conception of the human condition (including a view of the actual position human beings find themselves in and a vision of their ideal position congruent with the view of ultimate reality), and a guide to the practical structuring of a human life aimed at its transformation from its actual to its ideal position. Spiritual well-being, then, is conceived as the spiritual life that is going well for a person. A pantheistic account that includes each of the three components of the spiritual life is presented. Therefore, we arrive at a pantheistic account of spiritual well-being, and this undercuts common objections to pantheism.